IJAZAH SANAD TRADITION IN PESANTREN, AN EFFORT TO MAINTAIN THE AUTHENTICITY OF ISLAMIC TEACHINGS (Study in Pesantren Maslakul Huda, Kajen, Pati, Central Java) - Lutfan Muntaqo (LP3M Universitas Sains Al Qur'an, 2018)
The reading of the Ijazah Sanad is one of the traditions in the pesantren (Islamic boarding school) world. Sanad is an effort tomaintain the scientific chain to be guaranteed and authentic directlyfrom the original source. Without a clear scientific chain, it is fearedthat learners do not reach the understanding intended by the writersof classical Islamic works such as tafsir, hadith, fiqh, nahwu and so on.Ijazah Sanad is an effort to maintain the authenticity of Islamicteachings. Pesantren Maslakul Huda is one of the pesantren which isvery strong in maintaining this tradition. Especially when it led byal-Maghfurlah KH. Sahal Mahfudh. The tradition lasted until nowin the hands of his successor.